Model Partisipatif Mahasiswa KKN Dalam Pendataan Kependudukan Sebagai Fondasi Pengembangan Sistem Informasi Desa (SID) Menuju E-Government di Desa Teratak, Kabupaten Lombok Tengah - Wahyu Astiko; Rahmatullah Rahmatullah; Khusnul Fajriansyah; Baiq Kautsar Zohratul Alya; Hanifah Hanifah; Atun Putriani; Amelia Putri Mujianda; Ro’iatul Fadilah; Jannatul Adni; Kiki Juniati Ratna Dewi; M. Asrori Imam Muhtada (Jurnal Gema Ngabdi, 2026)
Teratak Village, North Batukliang District, Central Lombok Regency, faces challenges in population data management, which is still conducted manually and has not been integrated into a digital system. This condition affects the effectiveness of administrative services and the accuracy of village development planning. This community service activity aimed to strengthen the village population database through the participatory model of Universitas Mataram Community Service Program students as a foundation for developing the Village Information System and supporting e-government-based governance. The activity was conducted from December 2025 to February 2026 through several stages, including institutional coordination, Family Card data collection, data verification with village officials and hamlet heads, data digitization, and hamlet potential mapping through interviews. The results showed that population data collection successfully covered 10 hamlets, with a total of 5,911 residents and 1,506 households. The collected data were compiled into a digital Village Information System database to support administrative service efficiency, information transparency, and data-based development planning. The main challenges included limited community trust and digital literacy.